2005
DOI: 10.1111/j.1600-0625.2005.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid induces apoptosis in skin cancer cells and differentiation in normal human keratinocytes

Abstract: Betulinic acid (BA), a pentacyclic triterpene of plant origin, induces cell death in melanoma cells and other malignant cells of neuroectodermal origin. Little is known about additional biological effects in normal target cells. We show, in this study, that BA induces differentiation as well as cell death in normal human keratinocytes (NHK). Cytotoxicity profiles of BA are compared among normal human keratinocytes, HaCaT cells, IGR1 melanoma cells and normal melanocytes. As expected, BA is toxic to all cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 46 publications
5
48
0
1
Order By: Relevance
“…Moreover, because betulinic acid induces many other cytotoxic and proapoptotic effects in cancer cell lines (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), it is likely that down-regulation of Sp proteins differentially contributes to the overall effect of this compound. Current studies with betulinic acid are investigating tumor-type similarities and differences in its mechanism of action and the development of more potent analogues for clinical applications in the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because betulinic acid induces many other cytotoxic and proapoptotic effects in cancer cell lines (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), it is likely that down-regulation of Sp proteins differentially contributes to the overall effect of this compound. Current studies with betulinic acid are investigating tumor-type similarities and differences in its mechanism of action and the development of more potent analogues for clinical applications in the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that betulinic acid induces apoptosis in several different cancer cell lines through multiple pathways, which include direct effects on the mitochondria accompanied by decreased mitochondrial membrane potential, up-regulation of death receptors, and interactions with other agents (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). In addition, betulinic acid exhibits antiangiogenic activity in an in vitro assay for tube-like structures in ECV304 cells (48); however, the underlying mechanisms of action for these responses are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…antibacterial, antiviral, anti-parasite BE: [5,6]; BA: [7][8][9]; BE/BA: [10,11]; BE/BA/OA: [12]; LU/BA: [13]; OA/BA: [14] hepatoprotective BE: [15]; BE/BA: [16]; OA: [17][18][19][20]; LU: [21]; BA: [22] antitumor BE: [23,24]; BA: [25,26] BE/BA: [27,28]; LU: [29]; OA: [18,19,30] wound healing extract: [31][32][33]; BA: [34]; OA: [35,36] anti-inflammatory BE: [5,37]; LU: [38,39]; OA: [18,40] Apart from these pharmacological effects, birch bark extract is able to act as a gelling agent and Pickering emulsifier [41][42][43]. Together with its anti-inflammatory and wound healing effects, this makes birch bark dry extract interesting for the stabilisation of semisolid systems, such as gels and creams, acting as an active ingredient and an excipient in parallel.…”
Section: Pharmacological Effects Of Triterpenoids Contained In Birchmentioning
confidence: 99%
“…Apoptosis is usually associated with cytoplasm shrinkage, nuclear alteration and DNA breakage [10] . And betulinic acid was also found to induce apoptosis of malignant melanoma [11] .…”
Section: Discussionmentioning
confidence: 99%